If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -1) = 7x + 1 Reorder the terms: 5(-1 + 3x) = 7x + 1 (-1 * 5 + 3x * 5) = 7x + 1 (-5 + 15x) = 7x + 1 Reorder the terms: -5 + 15x = 1 + 7x Solving -5 + 15x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 15x + -7x = 1 + 7x + -7x Combine like terms: 15x + -7x = 8x -5 + 8x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + 8x = 1 + 0 -5 + 8x = 1 Add '5' to each side of the equation. -5 + 5 + 8x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 8x = 1 + 5 8x = 1 + 5 Combine like terms: 1 + 5 = 6 8x = 6 Divide each side by '8'. x = 0.75 Simplifying x = 0.75
| 21+22x=35+15x | | -8x+3x=32+36x | | 6(a+3)=8+6a | | 20x-4=64 | | (x+10)(x+10)=11 | | 9a=16*96 | | 20x+90=10x+120 | | 2x+10=50-8x | | 5+5x+1-3x=-4+6x+5-5x | | 60+42+x=180 | | -6/113/4 | | 448x^4-175x^2y^2= | | 42-5x=28-2x | | 15x^2-6x=153 | | 4k-3=7 | | 30+64=4x-6 | | 1.5X-6=50 | | 2-z=-2 | | 31/2x(1-3)^4 | | 8y-2y=60 | | 3x+7=28-2x | | 6(y-1)=2y+8 | | 4/53/8 | | 5x=12x-6x | | 0.25x+0.1y=1.8 | | 1/31/4 | | 9x-6l=-16 | | 0.8-4(b-1)=0.2+3(4-3) | | -4.9x^2+90x=0 | | (a+1)=9 | | 5/8/2/4 | | 5X+5H+1-(5X+1)= |